(untitled) (The Himalayan Geographers, 2023)
From the ancient time, Nepal is a multi-ethnic, multi-lingual, multi–religious, and multi-cultural country. This Himalayan country offers the world communities rich cultural heritage, natural beauty and legendary images with historical. It has always already been proven that the brave Nepali people sacrificed their lives for national unity, territorial integrity and the world international peace. Despite its size Nepal is rich with geographical, social, religious, and cultural diversities let alone ethnic variety with the perfect harmony. People celebrate various festivals and jatras (carnivals) during different seasons. The people from various castes and ethnic communities with various feasts and festivals, rites and rituals, and myths and ethnicity have made immense contribute for the nation building. Gurung is one of the rich indigenous ethnic communities in Nepal which in recent decades has suffered severe problem of brain drain because of an increasing trend of globalization as well as their recruitment in foreign armies. Descending from hills of Nepal, Gurungs as mercenary soldiers in foreign armies, including the British, Singapore and Indian have made immense contribution to the formation of Nepali Diaspora in Asia and beyond. Such an increasing trend of formation and expansion of the diaspora has adversely resulted in the brain drain from Nepal, a severe challenge to Nepal’s plan of progress and prosperity.